A educação e a sustentabilidade: o desafio de um paradigma e a década da educação para o desenvolvimento sustentável da UNESCO (2005-2014) - Bastos, Alexandre Marucci [UNESP]; Souza, Cláudio Benedito Gomide de [UNESP] (My University, 2013)
This paper aims at proposing a discussion on the role of education in a pragmatic plot. It intends to offer some contributions to the consolidation in the essence of sustainable development and of a contextualized sustainability as well as its respective dimensions. Therefore, some conceptual evolutions of such expressions and the implications for when they are being used, especially parallel to the UN Decade of Education for Sustainable Development, UNESCO (2005-2014) are presented. This paper also intends to promote some reflection on how much environmental and general education are important with regard to the challenge of multidimensional balance proposed, as seen from the perspective of a paradigm that has been constantly shaped since the Stockholm Conference of 1972, going through the given contributions in 1992 by The Earth Summit in Rio de Janeiro – Eco 92 / Rio 92; and from there to the United Nations Conference on Sustainable Development, of Rio+20, in 2012.

Este trabalho pretende propor uma discussão sobre o papel da educação no enredo de um pragmatismo, pelo qual venha oferecer algumas contribuições para a consolidação da essência de um desenvolvimento sustentável e de uma contextualizada sustentabilidade, bem como de suas respectivas dimensões. Para tanto, são apresentadas algumas evoluções conceituais de tais expressões e as implicações quando de suas utilizações, sobretudo em paralelo à Década da Educação para o Desenvolvimento Sustentável da ONU/UNESCO (2005-2014); na expectativa de promover uma reflexão sobre o quanto a educação, não apenas a ambiental, mas em seu sentido mais amplo, se faz fundamental diante o desafio proposto por um equilíbrio multidimensional, visto pela perspectiva de um paradigma que vem sendo continuamente moldado desde a Conferência de Estocolmo, de 1972; passando pelas contribuições propiciadas, em 1992, pelo Grande Encontro da Terra – Eco 92 / Rio 92; e daí seguindo-se até a Conferência das Nações Unidas sobre Desenvolvimento Sustentável, a Rio+20, na cidade do Rio de Janeiro, em 2012.
Education and sustainability: the challenge of a paradigm and the decade of education for sustainable development UNESCO (2005-2014)
Keywords: Education; Education for sustainable development; Environmental education; Sustainable development; Sustainability; Dimensions of sustainability; Educação; Educação para o desenvolvimento sustentável; Educação ambiental; Desenvolvimento sustentável; Sustentabilidade; Dimensões da sustentabilidade